56 PROLACTIN ALTERS BCR-MEDIATED APOPTOSIS AND RECEPTOR EDITING. (1st March 2007) - Peeva, E.; Rosenfeld, G. E.; Gonzalez, J.; Saha, S.
Abstract : Background: Autoreactive lymphocytes are constantly generated and eliminated to maintain tolerance. Two major mechanisms for tolerance induction are deletion and receptor editing. In the spleen, the majority of negative selection occurs in transitional B cells, mainly in the T1 B-cell subset, resulting in a T1:T2 ratio > 1. We have shown that prolactin-altered negative selection of autoreactive specificities allows for survival and activation of DNA-reactive B cells and development of lupus in mice that do not develop lupus spontaneously. In BALB/c mice, treatment with prolactin decreases the number of T1 B cells and increases the number of T2 B cells leading to a T1/T2 ratio < 1, which indicates that prolactin impairs negative selection. Purpose: The aim of this study is to characterize the mechanisms by which prolactin breaks B-cell tolerance. Deletion and receptor editing as means of negative selection were examined using a combination of flow cytometry and real-time PCR experiments. Methods: Eight- to 10-week-old female BALB/c mice were treated with prolactin (100 μg/d) or placebo (normal saline) for 1 month. Splenocytes were isolated, and RBC lysis was performed. Flow cytometric measurement of anti-IgM Ab-induced apoptosis was used to determine the effect of prolactin on BCR-mediated deletion in transitional T1 (CD19 + AA4.1 + CD21 − CD23 − ) and T2 (CD19 + AA4.1 + CD21 + CD23 + ) B-cell subsets. The effect of prolactin on receptor editing was evaluated by RAG-1 and RAG-2 mRNA expression and the presence of kappa/lambda-positive B cells. RNA was isolated by RNAeasy kit from B cells purified with Dynabeads. RAG-2 mRNA expression was determined by real-time PCR. Flow cytometry was used to determine the number of B cells coexpressing kappa/lambda light chains in the transitional T1 and T2 and mature marginal zone (MZ) (CD19 + AA4.1 − CD21 + CD23 − ) and follicular (Fo) (CD19 + AA4.1 − CD21intermediateCD23 + ) B-cell subsets. The real-time data were obtained by a Light Cycler real-time PCR machine. Flow cytometry data were acquired by an LSRII flow cytometer, and data analysis was done by FlowJo software. Results: After BCR stimulation with anti-IgM antibody (10 μg/mL) as a surrogate antigen, T1 B-cell subset from prolactin-treated mice showed significantly less annexin V-positive B cells than the T1 subset from placebo-treated mice ( p = .023). As per our microarray data, this effect of prolactin on B-cell deletion may be mediated by prolactin-induced overexpression of the antiapoptotic molecules Bcl-2, Birc-1, and/or IFNalfaR. In addition, treatment with prolactin induced a two- and threefold increase in RAG-1 and RAG-2 mRNA expression in B cells ( p = .012), as well as an elevated number of kappa/lambda-expressing B cells with T2 ( p = .028) and Fo ( p = .001) phenotype, an indication of continued receptor editing. Conclusion: Treatment with prolactin increases the resistance to anti-IgM-mediated apoptosis of T1 B-cell subsets, which, under normal circumstances, is a commonplace for negative selection of the autoreactive specificities. The failed ability to delete by apoptosis may explain the increased survival of self-reactive B cells destined for deletion. In addition, increased serum prolactin levels lead to increased receptor editing in splenic B cells, and the V(D)J recombination in the peripheral lymphoid organs has been associated with generation of pathogenic autoantibodies and autoimmunity. Thus, alterations of both BCR-mediated deletion and receptor editing may be implicated as mechanisms in prolactin-induced breakdown of B-cell tolerance.